Myokines as potential mediators of changes in glucose homeostasis and muscle mass after bariatric surgery - Orioli, Laura; Thissen, Jean-Paul (Frontiers in Endocrinology, 2025)
Myokines are bioactive peptides released by skeletal muscle. Myokines exert auto-, para-, or endocrine effects, enabling them to regulate many aspects of metabolism in various tissues. However, the contribution of myokines to the dramatic changes in glucose homeostasis and muscle mass induced by bariatric surgery has not been established. Our review highlights that myokines such as brain-derived neurotrophic factor (BDNF), meteorin-like protein (Metrnl), secreted protein acidic and rich in cysteine (SPARC), apelin (APLN) and myostatin (MSTN) may mediate changes in glucose homeostasis and muscle mass after bariatric surgery. Our review also identifies myonectin as an interesting candidate for future studies, as this myokine may regulate lipid metabolism and muscle mass after bariatric surgery. These myokines may provide novel therapeutic targets and biomarkers for obesity, type 2 diabetes and sarcopenia.